Interfirm Profitability Differences: Comment - Caves, R. E.; Gale, B. T.; Porter, M. E. (Quarterly Journal of Economics, 1977)
Journal Article Interfirm Profitability Differences: Comment Get access R. E. Caves, R. E. Caves Harvard University Search for other works by this author on: Oxford Academic Google Scholar B. T. Gale, B. T. Gale University of Massachusetts Search for other works by this author on: Oxford Academic Google Scholar M. E. Porter M. E. Porter Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 91, Issue 4, November 1977, Pages 667–675, https://doi.org/10.2307/1885889 Published: 01 November 1977